2003
DOI: 10.1016/s0022-5223(03)00035-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of perioperative factors on outcomes in children aged less than 18 months after repair of tetralogy of Fallot

Abstract: Primary repair at an early age has excellent short-term outcome. Patients less than 3 months of age have an increased but transient intensive care unit morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 24 publications
4
49
1
Order By: Relevance
“…We identified age and weight as independent predictors of the length of ICU stay. Our finding is in agreement with the findings of van Dongen et al [13] and van Arsdell et al [20] who also identified younger age at time of TOF repair as an independent predictor of prolonged ICU stay, prolonged duration of mechanical ventilation, and prolonged inotropic support.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We identified age and weight as independent predictors of the length of ICU stay. Our finding is in agreement with the findings of van Dongen et al [13] and van Arsdell et al [20] who also identified younger age at time of TOF repair as an independent predictor of prolonged ICU stay, prolonged duration of mechanical ventilation, and prolonged inotropic support.…”
Section: Discussionsupporting
confidence: 94%
“…In spite of low surgical mortality, ICU morbidity is relatively common after primary TOF repair [13]. There is a strong correlation between ICU morbidity and intraoperative factors such as cardiopulmonary bypass (CPB) time, cross clamp, and surgical techniques [3,11,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these findings are important and highlight the fact that 22q11.2DS results in increased morbidity, rather than mortality, in this particular patient population. 8,9, 25 The same may not be true in the more complicated cohort with major aorto-pulmonary collateral arteries requiring staged repairs as suggested by Mahle et al 7 …”
Section: Discussionmentioning
confidence: 95%
“…7 In addition, non-cardiac abnormalities and malformation syndromes appear to be independent risk factors for prolonged intubation, re-intubation and longer intensive care duration. 8, 9 Therefore, factors related to genotype influence outcomes.…”
Section: Introductionmentioning
confidence: 99%